The Effect of Kettlebell Swing Load and Cadence on Physiological, Perceptual and Mechanical Variables - Michael J. Duncan; Rosanna Gibbard; Leanne M. Raymond; Peter Mundy (Sports, 2015)
This study compared the physiological, perceptual and mechanical responses to kettlebell swings at different loads and swing speeds. Following familiarization 16 strength trained participants (10 males, six females, mean age ± SD = 23 ± 2.9) performed four trials: 2 min kettlebell swings with an 8 kg kettlebell at a fast cadence; 2 min kettlebell swings with an 8 kg kettlebell at a slow cadence; 4 min kettlebell swings with a 4 kg kettlebell at a fast cadence; 4 min kettlebell swings with a 4 kg kettlebell at a slow cadence. Repeated measured analysis of variance indicated no significant differences in peak blood lactate or peak net vertical force across loads and cadences (P > 0.05). Significant main effect for time for heart rate indicated that heart rate was higher at the end of each bout than at mid-point (P = 0.001). A significant Load X cadence interaction for rating of perceived exertion (RPE) (P = 0.030) revealed that RPE values were significantly higher in the 8 kg slow cadence condition compared to the 4 kg slow (P = 0.002) and 4 kg fast (P = 0.016) conditions. In summary, this study indicates that the physiological and mechanical responses to kettlebell swings at 4 kg and 8 kg loads and at fast and slow cadence were similar, whereas the perceptual response is greater when swinging an 8 kg kettlebell at slow cadence.